AppML : An Idea of Mordern Web Development (International Journal of Engineering and Computer Science, 2015)
AppML combines the most up-to-date techniques and ideas of modern web development. AppML is very easy to understand, and develop. AppML is not a programming language. It used to describe applications. By using  AppML you can create Internet applications without programming. AppML allows the programmer to redefine both data and functions while the application is running.Since AppML applications are written in XML, AppML applications are self-describing.In this paper ,we are just providing all the key concept related to AppML .